The Determinants of Value in the Philadelphia Housing Market: A Case Study of the Main Line 1967-1969 - Edelstein, Robert (The Review of Economics and Statistics, 1974)
Robert Edelstein, The Determinants of Value in the Philadelphia Housing Market: A Case Study of the Main Line 1967-1969, The Review of Economics and Statistics, Vol. 56, No. 3 (Aug., 1974), pp. 319-328